2019
DOI: 10.1021/jacs.8b13119
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study and Development of Catalytic Reactions of Sm(II)

Abstract: Despite the broad utility and application of SmI 2 in synthesis, the reagent is used in stoichiometric amounts and has a high molecular weight, resulting in a large amount of material being used for reactions requiring one or more equivalents of electrons. We report mechanistic studies on catalytic reactions of Sm(II) employing a terminal magnesium reductant and trimethyl silyl chloride in concert with a non-coordinating proton donor source. Reactions using this approach permitted reductions with as little as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 77 publications
1
21
0
Order By: Relevance
“…Recently, Flowers reported a detailed mechanistic study on the development of catalytic reaction using a chemical approach [15] . Surprisingly, this study showed that presence of non‐coordinating alcohols (such as TFE, t‐BuOH) significantly enhances the rate of catalytic reaction as well as catalytic stability.…”
Section: Approaches In Developing Catalytic Reactions With Smi2mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Flowers reported a detailed mechanistic study on the development of catalytic reaction using a chemical approach [15] . Surprisingly, this study showed that presence of non‐coordinating alcohols (such as TFE, t‐BuOH) significantly enhances the rate of catalytic reaction as well as catalytic stability.…”
Section: Approaches In Developing Catalytic Reactions With Smi2mentioning
confidence: 99%
“…While SmI 2 has its unique ability to carry out reductive transformations, development of catalytic reactions of this reagent continues to be a challenging problem. Several factors such as i ) poor solubility of Sm 3+ , ii ) inertness of Sm 3+ towards reduction, iii ) ligand exchange reactions in Sm coordination sphere pose significant challenges in developing a sustainable and robust catalytic procedure [15] …”
Section: Approaches In Developing Catalytic Reactions With Smi2mentioning
confidence: 99%
See 3 more Smart Citations